Interceptação da luz e simulação da fotossíntese em cajueiro anão - Duarte, Thiago Franco (2016)
The light interception and photosynthesis are determining processes of crop yield. The study of these processes are necessary steps in the build of crop models. For dwarf cashew, considering the whole tree, there is not study of this nature. Thus, the aim of the work was evaluate and validate the light interception model of CHARLES-EDWARDS & THORNLEY (1973) and, further, simulate the photosynthesis for whole tree with the model of THORPE et al. (1978). The light measurements necessary for model validation, were realized in orchard of adult dwarf cashew tree, localized in Baixada Cuiabana (15,8º S; 56,1º W). The evaluation of light interception model was made in intervals of 60, 120, 180, 240 e 300 min. In temporal scale of 60 min there was tendency of underestimate the measured data. In scale of 300 min, the simulation was the most near of measured data, with determination coefficient of: 0.90; accuracy coefficient: 0.96; performance index: 0.91 and mean absolute percent error: 5.65. Was simulated the effect of row azimuth on light interception using the model of CHARLES-EDWARDS & THORPE (1976), for sites with latitudes of 0, -5, -10, e-15. In addition, was derived a new geometric model of light interception for plants in the orchard and was assessed the effect of the change in the planting spacing on light interception. There has been greater light interception in East-West direction (90° in relation to the North), although with little significant differences in relation to the other. The minimum spacing required so there is no competition for light between plants grown in the orchard is 50 m2 , for a square arrangement of planting. For simulating photosynthesis in whole tree crown, it was first assessed ten models of net photosynthetic light response-curves for sun and shaded leaves. These measurements were made in field conditions, in fully expanded leaves located on the outside and inside of the tree crown (sun and shaded leaves).The implemented models for simulating photosynthesis for tree crown were the models of PRIOUL & CHARLIER (1974) and YE (2007) for sun and shaded leaves respectively. The simulation of photosynthesis of adult dwarf cashew tree with the model THORPE et al. (1978), considering a leaf area density geometrically uniform in whole tree, notice that, in function of lower availability of light, the higher leaf area located in inner part of tree have lower rate of photosynthesis during the day, comparing with the leaves located in extremity of tree. Furthermore, the net photosynthesis of whole tree reduces with diffuse fraction of global radiation. Altering the leaf area density and its location in the tree, noticed that, in adult cashew tree, there is tendency of increase of photosynthesis with increase of leaf density, and in tree that have leaf area only in extremity of tree, have higher photosynthetic rate with higher leaf area density.